TATA KELOLA DESTINASI WISATA PANTAI BATU WARNA DI KOLBANO(STUDI PARTISISPASI MASYARAKAT DALAM MENGELOLA WISATA PANTAI BATU WARNA DI DESA SPAHA, KECAMATAN KOLBANO, KABUPATEN TIMUR TENGAH SELATAN) - Nabuasa, Selin; Sabaat, Yeftha Yerianto; Baso, Boli Tonda (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The management of Kolbano Beach destination in Spaha Village is located in South Central Timor Regency and has great tourism potential with the beauty of unique colored rocks. For its good and beneficial development, comprehensive and sustainable governance is needed. Kolbano Beach can also be improved so that it can provide economic and social benefits that develop for the people of Spaha Village and its surroundings as well as public awareness. The problem studied in this study is the management of Kolbano tourism managed by the local community without the intervention of the Village government, where until now Kolbano tourism has not developed as seen from its management itself. The method used is a qualitative descriptive method because researchers can obtain direct statements from informants regarding someone's experiences, opinions, feelings and knowledge about something. Although there is no government intervention, the government has taken the initiative to provide information related to Kolbano tourism through print media and electronic media such as: website, Youtube, FB, IG and Tik Tok. From the results I got, Kolbano tourism management has a lot of time to plan how tourism development in Spaha Village can strengthen cooperation and improve quality human resources.